Influence of the evolution of high-speed railway infrastructure on the success of Italian liberalization. Issue 2 (June 2019) - Olarte Bacares, Carlos Augusto; Brunel, Julien; Sigaud, Damien
The arrival of a new operator on the Italian high-speed railway (HSR) market, its maintanance and its market share made Italian open access experience one of the most successful liberalization models in the HSR sector. Researchers noticed that since the entry of the new operator, expansion of Italian HSR market is mostly due to the presence of this new operator. The aim of this article is to establish whether there were some other characteristics of the Italian HSR market that may explain this success even if it may be in opposition with what theory commonly suggests about competition in HSR markets. This research tries to do a complementary analysis by making a comparison with another successful HSR market that is not already liberalized: the French HSR market. After retracing supply, demand and markets maturity of Rome–Milan and Paris–Marseille lines, results reveal that supply and demand evolutions in both markets were very similar, if not identical after the commissioning of HSR. It suggests that liberalization may not be the only explanation of the significant evolution of Italian HSR market but that the opening of new infrastructures may also lead to positive trends that remain until markets reach a high level of maturity. This maturity understood as the residual capacity of the network and partially determined by infrastructure improvement seems to be another variable that had influenced the success of NTV. Indeed, before liberalization, Italian HSR network was far from saturation that allowed new entrant to capture important market shares.